2022
DOI: 10.1111/cbdd.14148
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive review on natural pharmacophore tethered 1,2,3‐triazoles as active pharmaceuticals

Abstract: The privileged 1,2,3‐triazole scaffold is drawing researcher's attention due to its widespread applications in diverse fields such as drug discovery (e.g., carboxyamidotriazole), organic synthesis (click‐reaction template), polymeric materials (e.g., triazolamer), supramolecular receptors (e.g., triazolophane), fluorescent materials (e.g., metal–organic frameworks), and agricultural sectors (e.g., fungicides). Various 1,2,3‐triazole persuasion modules are also currently available in the market that have multip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 85 publications
0
15
0
Order By: Relevance
“…The change in the solvent led to the decrease in conversion compared to the one in DCM (entries 9,11,13,15,17), and heating the reaction mixture in most cases resulted in decomposition of the organic material (entries 3,5,6,10,14,16). The attempts to perform the reaction without catalyst under conventional heating led to the very slow conversion of azide 2 into triazole 3 (entries [20][21][22]; microwave activation for 1 h did not promoted the cycloaddition (entry 23). Up to today, a number of preparative modifications of CuAAC reactions have been elaborated [1,2,47] and the use of diverse sources of catalytically active Cu(I) was reported, including Cu(I)-complex salt, Cu(I)-containing dendrimers, Cu-nanoparticles, and other molecular frameworks [48].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The change in the solvent led to the decrease in conversion compared to the one in DCM (entries 9,11,13,15,17), and heating the reaction mixture in most cases resulted in decomposition of the organic material (entries 3,5,6,10,14,16). The attempts to perform the reaction without catalyst under conventional heating led to the very slow conversion of azide 2 into triazole 3 (entries [20][21][22]; microwave activation for 1 h did not promoted the cycloaddition (entry 23). Up to today, a number of preparative modifications of CuAAC reactions have been elaborated [1,2,47] and the use of diverse sources of catalytically active Cu(I) was reported, including Cu(I)-complex salt, Cu(I)-containing dendrimers, Cu-nanoparticles, and other molecular frameworks [48].…”
Section: Resultsmentioning
confidence: 99%
“…The change in the solvent led to the decrease in conversion compared to the one in DCM (entries 9,11,13,15,17), and heating the reaction mixture in most cases resulted in decomposition of the organic material (entries 3,5,6,10,14,16). The attempts to perform the reaction without catalyst under conventional heating led to the very slow conversion of azide 2 into triazole 3 (entries [20][21][22]; microwave activation for 1 h did not promoted the cycloaddition (entry 23). Isomeric azidoalcohol 2b was involved in the cycloaddition with phenylacetylene in the catalytic conditions to yield triazole 4 (Scheme 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The extensive biological activities of 1,2,3-triazoles (such as antibacterial characteristics, anti-inflammatory, and anticancer properties) have introduced them as an important category of synthons and building blocks in medicinal chemistry and pharmaceutical science 32 36 . The biological evaluation demonstrated that introducing chiral triazole cores in the scaffold of biological materials may allow greater results in enantioselective bioactivity 37 , 38 .…”
Section: Introductionmentioning
confidence: 99%
“…A vast amount of experimentation and literature reports on novel antimicrobial 1,2,3-triazoles has been accumulated over the years and the pace of research efforts seems to only accelerate. For example,’s sake, the authors of this article present several very detailed reviews on antimicrobial triazoles, published just over the past few years ( Zhang, 2019 ; Xu, 2020 ; Deng et al, 2022 ; Li and Zhang, 2022 ; Rammohan et al, 2023 ). Transition metals have played a part in medicine for millenia now.…”
Section: Introductionmentioning
confidence: 99%